2008
DOI: 10.1007/s10750-008-9395-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of hydropower installations and associated river regulation on River Shannon eel populations: mitigation and management

Abstract: The Shannon, Ireland's largest river, is used for hydroelectricity generation since 1929. Subsequently, the Electricity Supply Board assumed responsibility for management of its eel stocks, due to the impact of the hydro-dam on recruitment to the commercial fishery. In order to negate a decline in juvenile recruitment resulting from the installation of hydroelectric facilities, management was focused on stocking lakes with elvers and fingerling eels. These were trapped at the hydropower facilities and in estua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 9 publications
1
47
0
Order By: Relevance
“…Several studies have shown the negative impacts of hydropower on adult silver eels, with mortalities ranging from 5 to 100% in the case of old turbines (see review by McCarthy et al 2008). Because European eels are classified as an Endangered species, conservation measures have been recommended by the European Union.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the negative impacts of hydropower on adult silver eels, with mortalities ranging from 5 to 100% in the case of old turbines (see review by McCarthy et al 2008). Because European eels are classified as an Endangered species, conservation measures have been recommended by the European Union.…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that there are more than 1600 lakes in the river basin district. The area includes about 73 % agricultural land and 12 % wetland, mostly peatland habitat (McCarthy et al 2008, Gharbia et al 2016Assessment 2012Assessment , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…1) drains an area of approximately 11,700 km 2 , before flowing into the sea at Limerick. The gradient is remarkably low, with the river rising at about 152 m above sea level and then flowing southwards with only a 12-m drop in altitude over 185 km, before finally descending more rapidly to sea level (Gharbia et al 2016;Assessment 2012Assessment , 2013McCarthy et al 2008). The potential impacts of climate change are of most concern where water resources are either heavily allocated or particularly vulnerable to changes in rainfall (Kulkarni et al 2011), in addition to risks due to extreme events (Engler and Werner 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The various phases of the CMIP have grown steadily as testified both in terms of participants' number and scientific impacts [16]. In this study, climate change projections for the Shannon River [17,18] catchment are presented for several temperature and precipitation from multi-GCM ensembles for three future time intervals using a range of different Representative Concentration Pathways (RCPs). The projection process used a statistical downscaling procedure based on statistical relationships linking a set of large-scale atmospheric variables to regional climate variables in an observational calibration period.…”
Section: Introductionmentioning
confidence: 99%